Slow Cenozoic uplift of the western Andean Cordillera indicated by cosmogenic 3He in alluvial boulders from the Pacific Planation Surface. Issue 20 (29th October 2015) - Evenstar, Laura A.; Stuart, Finlay M.; Hartley, Adrian J.; Tattitch, Brain
Abstract: To determine the mechanisms responsible for mountain belt growth, it is important to accurately establish the timing of surface uplift. Here we exploit the altitude control on the production rate of in situ cosmogenic nuclides to test the hypothesis that the Andes was uplifted in the late Miocene. High concentrations of in situ cosmogenic 3 He ( 3 Hecos ) have previously been measured in alluvial boulders on the western flank of the Central Andes, northern Chile (Evenstar et al. 2009). These are consistent with deposition soon after formation of the surface (13–14 Ma). We have modeled the accumulation of cosmogenic 3 He in several different surface uplift scenarios and compared them to the measured concentrations. The measured 3 Hecos concentrations are too high to be produced by late Miocene uplift and imply that the western flank of the Andean Cordillera attained a substantial part of its current elevation prior to 14 Myr ago. Key Points: Production rates of in situ cosmogenic isotopes are used for paleoelevation Uplift of the Andes by mantle delamination in the late Miocene is ruled out The Precordillera attained a substantial part of its elevation by 14 Ma